A circular argument - Frödén, Martin Cathcart (Emerald Publishing Limited, 2021)
Part one, A Circular Argument, is informed by a series of reflections on the author's work as a prison teacher. Delving into the obsession with the circular as an architectural gesture and as a concept combining containment and transparency, the author examines spatial hierarchies across time, from the ideal planned city of the Middle Ages, to the all-seeing eye of modern digital society. Part two, The Out, follows the fictional story of a disgruntled architect, a clever prisoner and an ingenious escape plan. Exploring how the complications and surprises of human interaction colour and change the supposedly watertight systems of social control society designs, the novel disrupts how we might think about space and power. Injecting new energy and creative perspectives into traditional academic research, this practice-led book is an innovative exploration between critical and creative approaches, and between multiple social and spatial hierarchies.
Includes index.
Keywords: Architecture and society.; Space.; Power (Social sciences); Criminal anthropology.; Social control.; Architecture -- General.; Theory of architecture.; elektronické knihy; electronic books